1998
DOI: 10.1007/s11666-006-5010-x
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Study of HP/HVOF Deposited WC-Co Coatings

Abstract: The deposition parameters of WC-17%Co coatings produced using the JP-5000 liquid-fuel HP/HVOF system (Eutectic TAFA) were investigated with the initial purpose of parameter improvement and optimization. The coating microstructures, porosities, phase compositions, and abrasion resistance were characterized. Preliminary work using the Taguchi statistical experimental design method aimed at optimizing the spray parameters in terms of the microstructure and phase composition was unsuccessful. The variations in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 2 publications
0
20
0
Order By: Relevance
“…The online diagnostic techniques supplemented with other measurement tools have significantly facilitated the development of process maps for HVOF process optimization. These experimental investigations studied the effect of operating parameters including gun type, fuel type, feedstock type and size, combustion pressure, fuel/ oxygen ratio, spray distance on the particle temperature, velocity, melting ratio, oxidant content and the resulting coating microstructure, porosity, hardness, wear abrasion, and corrosion resistance (e.g., Ref 3,28,34,[48][49][50]61,62,65,71,[81][82][83][84][85][86][87][88][89][90][91][92]. The experimental studies have been supplemented by CFD modeling efforts (Ref 10-13, 15-21, 23), which provide fundamental understanding of the gas dynamics, particle in-flight, and impact.…”
Section: Control Of Hvof Thermal Spraymentioning
confidence: 99%
“…The online diagnostic techniques supplemented with other measurement tools have significantly facilitated the development of process maps for HVOF process optimization. These experimental investigations studied the effect of operating parameters including gun type, fuel type, feedstock type and size, combustion pressure, fuel/ oxygen ratio, spray distance on the particle temperature, velocity, melting ratio, oxidant content and the resulting coating microstructure, porosity, hardness, wear abrasion, and corrosion resistance (e.g., Ref 3,28,34,[48][49][50]61,62,65,71,[81][82][83][84][85][86][87][88][89][90][91][92]. The experimental studies have been supplemented by CFD modeling efforts (Ref 10-13, 15-21, 23), which provide fundamental understanding of the gas dynamics, particle in-flight, and impact.…”
Section: Control Of Hvof Thermal Spraymentioning
confidence: 99%
“…In order to improve the operation of the HVOF thermal spray process, much experimental work has been done in the last decade to study the effect of operating parameters including gun type, fuel type, feedstock type and size, combustion pressure, fuel/oxygen ratio and spray distance on the particle temperature, velocity, melting ratio, oxidant content and the resulting coating microstructure, porosity, hardness, wear abrasion and corrosion resistance (e.g., de Villiers Lovelock et al, 1998;Gil and Staia, 2002;Gourlaouen et al, 2000;Hanson et al, 2002;Hanson and Settles, 2003;Hearley et al, 2000;Khor et al, 2004;Legoux et al, 2002;Lih et al, 2000;Lugscheider et al, 1998;Marple et al, 2001;Planche et al, 2002;Qiao et al, 2003;Suegama et al, 2005;Swank et al, 1994a,b;Wirojanupatump et al, 2001;Zhao et al, 2004). Because of the inherent complexity of the process, a fundamental understanding of the physicochemical phenomena involved in the HVOF thermal spray process generally requires comprehensive numerical models including computational fluid dynamic (CFD) models (e.g., Chang and Moore, 1995;Cheng et al, 2001a,b;Dolatabadi et al, 2003;Gu et al, 2001;Hassan et al, 1998;Kamnis and Gu, 2006;Lopez et al, 1998;Oberkampf and Talpallikar, 1996;Power et al, 1991;Yang and Eidelman, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…3) revealed a good adhesion between the coating layer and the substrate for the specimens. The high velocity impact of semi-molten coating materials to the substrate accompanies severe plastic deformation and rapid solidification, therefore thermal spray coating layers are likely to possess inevitable pores and microcracks [16]. It is not difficult to be found that the Ni60/WC composite coating is not uniform in the microstructure.…”
Section: Resultsmentioning
confidence: 99%